2021
DOI: 10.1126/sciadv.abc4189
|View full text |Cite
|
Sign up to set email alerts
|

Nonresonant powering of injectable nanoelectrodes enables wireless deep brain stimulation in freely moving mice

Abstract: Devices that electrically modulate the deep brain have enabled important breakthroughs in the management of neurological and psychiatric disorders. Such devices are typically centimeter-scale, requiring surgical implantation and wired-in powering, which increases the risk of hemorrhage, infection, and damage during daily activity. Using smaller, remotely powered materials could lead to less invasive neuromodulation. Here, we present injectable, magnetoelectric nanoelectrodes that wirelessly transmit electrical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 49 publications
(79 reference statements)
3
112
0
Order By: Relevance
“…However, their utility as tools for neuropsychiatric treatment and investigation is less defined. While intracranial or deep brain MNP stimulation has mostly been validated with motor behaviors (55), these particles may be a valuable tool for creating and/or manipulating models of neuropsychiatric disorders (43,56). For instance, MNP stimulation of the prelimbic cortex reduced immobility in the forced-swim test and increased sucrose consumption in stressed mice (56).…”
Section: Discussionmentioning
confidence: 99%
“…However, their utility as tools for neuropsychiatric treatment and investigation is less defined. While intracranial or deep brain MNP stimulation has mostly been validated with motor behaviors (55), these particles may be a valuable tool for creating and/or manipulating models of neuropsychiatric disorders (43,56). For instance, MNP stimulation of the prelimbic cortex reduced immobility in the forced-swim test and increased sucrose consumption in stressed mice (56).…”
Section: Discussionmentioning
confidence: 99%
“…(Chen et al, 2018). (Middle) Piezoelectric nanoparticles can activate neurons when they are powered using an external magnetic field (Kozielski et al, 2021) or ultrasound (Marino et al, 2015). No genetic modification is needed for this method.…”
Section: Ultrasonically Powered Systemsmentioning
confidence: 99%
“…This approach involves the use of magnetoelectric nanoparticles (MENPs) produced from magnetostrictive CoFe 2 O 4 nanoparticles coated with piezoelectric BaTiO 3 (Kozielski et al, 2021). In vivo studies have demonstrated that MENPs injected cells can be activated under remote non-resonant frequency magnetic stimulation, which is sufficient to cause neural activation to change animal behavior.…”
Section: Magnetoelectric and Magnetothermal Stimulation By Injectable Nanoparticlesmentioning
confidence: 99%
“…In cancer theranostics, for example, nanomaterials are mainly used as environmentally-sensitive carriers of drugs or bioactive molecules, and can be actively or passively targeted to tumor cells, while ignoring healthy tissue. For neurostimulation, however, the nanomaterials themselves are typically the cargo, so that they may act as nanotransducers of external signals to modulate neuronal activity [17]. Similar properties have previously been exploited in clinically-approved thermal ablation procedures with magnetic iron oxide particles for some types of tumors [18].…”
Section: Introductionmentioning
confidence: 99%